Silabus Dalam Kurikulum KMMB - Ratna Sari; Muhammad Fadli; Suawaludin Suawaludin (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This research discusses how the syllabus is used in the KMMB curriculum. The curriculum is designed to prepare students to become active and responsible citizens, with an emphasis on developing critical thinking, problem solving, and social skills. The syllabus in the KMMB curriculum usually includes learning objectives, material to be taught, teaching methods, and assessment. Learning objectives usually include the knowledge, skills, and attitudes that students are expected to achieve. The material taught usually covers topics that are relevant to students’ daily lives and their communities. The teaching method in the KMMB syllabus usually involves an active approach, where students are given the opportunity to participate actively in the learning process. Assessments typically include formative and summative assessments, designed to measure student progress and teaching effectiveness. Overall, the syllabus in the KMMB curriculum is designed to support student-centred learning and the development of skills necessary for life in civil society.